Implicit Approximation Scheme for the Solution of K-Positive Definite Operator Equation - Naseer Shahzad; Arif Rafiq; Habtu Zegeye (Abstract and Applied Analysis)
We construct an implicit sequence suitable for the approximation of solutions of K-positive definite operator equations in real Banach spaces. Furthermore, implicit error estimate is obtained and the convergence is shown to be faster in comparsion to the explicit error estimate obtained by Osilike and Udomene (2001).